Nutrient Digestibility And Growth Rate Of Bull Calves Fed Rice Straw Treated With Wood Ash Extract - Rahman, MM; Akbar, MA; Islam, KMS; Khaleduzzaman, ABM; Bostami, ABMR (Bangladesh Journal of Animal Science, 2012)
An experiment was conducted for a period of 60 days with twelve bull calves with an average live weight of 77.78 ± 10.96 kg to determine the effect of treatment of rice straw with Wood Ash Extract (WAE) on feed intake, nutritive value, growth rate and economic benefits. The experimental animals were divided into three groups A, B and C having four animals in each. They were supplied randomly with three rations following randomized complete block design. All rations were made iso-nitrogenous by using urea as a source of nitrogen. Animals of group A were fed untreated rice straw, whereas, group B and C were fed urea-treated and WAE treated rice straw, respectively. The chemical analysis showed that treatment of rice straw with WAE increased ash content of straw from 13.93% to 16.45% and decreased the NDF content from 67.39% to 63.00%. The daily DM intake per 100 kg live weight of diet B was significantly (P<0.01) higher than that of diet A and C. The daily CP intake per 100 kg body weight of diet B (553.3g) was significantly (P<0.05) higher than that of diet A (449.5g). Similarly, the organic matter (OM) intake in bull calves fed diet B was significantly (P<0.05) higher than those fed diet A and C. The average daily live weight gain with diet B and C was significantly (P<0.01) higher than diet A. The animals fed diet B and C were more efficient in converting feed into live weight than animals fed diet A. Treating rice straw with wood ash extract improved the nutritive value, it significantly (P<0.01) increased the apparent digestibility of DM, OM, CP, ADF and NDF. It also increased the DCP, DOM, DNDF and DADF contents of rice straw compared with untreated straw. Although the total feed cost of untreated group is lower than those of WAE and urea-treated groups, the feed cost per kg live weight gain as well as the feed cost per kg meat production of WAE and urea-treated groups were significantly (P<0.01) lower than that of untreated rice straw. It may be concluded that nutrient composition and digestibility of rice straw and live weight gain of animals can be improved by treating rice straw with wood ash extract. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9911 BJAS 2009; 38(1-2): 42-52